2013
DOI: 10.1007/s13197-013-1161-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes in fish burger from Catla (Catla Catla) during refrigerated storage

Abstract: Fish burgers from catla (Catla catla) were assessed for proximate, chemical, microbiological and sensory quality changes over 17 days of refrigerated storage at 4 (±1)°C. The changes in proximate analysis of fish burgers were found to be significant at P <0.01. The values of peroxide value, free fatty acid, thiobarbutric acid and total volatile base nitrogen at the end of storage increased significantly at P <0.01 were determined as 4.98 (±0.22) meqO 2 /kg of fat, 0.94 (±0.01)% of oleic acid, 0.58 (± 0.02) mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 11 publications
15
30
0
Order By: Relevance
“…Moreover, significantly higher PV was noted in fish nuggets in comparison with surimi one ( p < .05). The same observation was also obtained by Vanitha et al () during the refrigerated studies of fish burger from catla with increasing PV to 7.28 meq/kg after 5 days of storage. Tokur, Polat, Beklevik, and Özkütük () also observed a significant increase in PV of tilapia fish burger during storage.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, significantly higher PV was noted in fish nuggets in comparison with surimi one ( p < .05). The same observation was also obtained by Vanitha et al () during the refrigerated studies of fish burger from catla with increasing PV to 7.28 meq/kg after 5 days of storage. Tokur, Polat, Beklevik, and Özkütük () also observed a significant increase in PV of tilapia fish burger during storage.…”
Section: Resultssupporting
confidence: 87%
“…During the whole storage period, the pH reached to 6.85 in surimi nuggets, while it was 6.75 in fish nugget. The reduction in pH might be related to the fermentation of some ingredient or due to the addition of spices (Vanitha et al, ). Additionally, the reduction in oxygen and enhancement of CO 2 content because of aerobic microflora growth might cause pH decline after three months (Mahmoudzadeh, Motallebi, Hosseini, Khaksar, et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…() reported that PV increased significantly in fish burgers prepared from deep flounder ( Pseudorhombus elevatus ) and brushtooth lizardfish ( Saurida undosquamis ) at the end of second month of storage. Moreover, the same results were reported by the Vanitha, Dhanapal, and Reddy () during the refrigerated studies of fish burger from Catla ( Catla catla ). The PV of fresh sample obtained 4.62 meqO 2 /kg and finally reached to 7.28 meqO 2 /kg.…”
Section: Discussionsupporting
confidence: 85%